HOW ASEAN ECONOMIC COMMUNITY (AEC) PROGRESS FROM EQUITY MARKET CORRELATION - Ferli, Ossi (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
This research aims to analyze the dynamic correlation by using stock prices daily data of 6 ASEAN equity markets during the period of 2007 until 2017 and then try to analysis the interdependence between markets. Empirical research using a Dynamic Conditional Correlation shows that there is a strong correlation in the countries of Indonesia, Malaysia, and Singapore; While correlation is still weak for Viet Nam. The study results also show from AR (1) and GARCH (1,1) model that the country of Indonesia, Malaysia, the Philippines, and Viet Nam have return period t equations is influenced significantly by return lag period before. It can be seen that all the countries of ASEAN 6 have variance period t equations is influenced significantly by the variance to previous period lag and lag error previous period lag. This is consistent with the time-varying volatility which indicates the persistence of very high volatility of stock return. The study result also shows that the interdependence between ASEAN 6 stock market seems still in high volatility, and the progress of correlation between the stock market did not have any significant leap as expected from the ASEAN Economic Community.